AN EXPOSITION OF ISLAMIC MEDICATION IN THE LIGHT OF THE QURAN AND HADITH - Akanni, Sanni Mukaila (European Scientific Journal, ESJ, 2013)
Islam is not only a religion but also a total way of life. It covers every aspect of human endeavour. So when addressing the issue of medication, Islam has a lot to say about it, ranging from its meaning and purpose, to its utilization and efficacy. Thus, in this paper effort is made to expose the Islamic concept of medication in the light of the Qur’an and Hadith, based on the following headings, aside the introduction and conclusion: The concept and principle of medication in Islam, the Qur’an and medication, the Hadith and medication and the forms of medication in Islam.